The Confluence of Time in Allende’s the House of the Spirits, Marquez’s One Hundred Years of Solitude, and Borges’s the Aleph and Other Stories - Al-Haidari, Ahmed Dhahi K .; Hadaegh, Bahee; Moosavinia, Sayyed Rahim (Journal of Ecohumanism, 2025)
This paper discusses how the concepts of time, history, and magical realism interlink in Allende’s The House of the Spirits, Márquez’s One Hundred Years of Solitude, and Borges’s collection of short stories, The Aleph and Other Stories. In each of these works, the author uses magical realism as a means to retell historical incidents and personal experiences, rewriting at least some historical options by nonlinearity, even to the level of philosophical questioning of those historical events. Allende interrelates political history with personal memory through fabulousness, criticising socio-political changes in Chile. Márquez shows time as repetitive; it is the way the Buendía family Trace repeats events related to the historical losses of Colombia. In contrast, the fragmentation of time and multiple realities is realized by Borges while he metaphysically contemplates identity and the nature of truth. This paper demonstrates how these authors converge in their use of magical realism to disrupt linear time and proffer alternative histories, while diverging in narrative technique and thematic focus. The research underlines the importance of the genre for reshaping cultural narratives and highlights the role of memory in constructing identity and confronting historical trauma.